Explanatory Models in Linguistics - Pere JuliÃ (Princeton University Press, 2014)
Contemporary students of language have two courses open to them: they can approach the subject matter as a natural phenomenon or they can consider it a formal object. In the first case, the relevant techniques of analysis are those of behavioral science. Language is behavior. An effective treatment requires that the activity of speaker and listener be systematically related to the independent variables of which it is a function. If, on the other hand, they choose to study language as an object, they must be aware of certain self-imposed limitations. Basic among these is the fact that they are not studying behavior but its traces, written or spoken. In bringing to bear the general outlook of the formal sciences on natural languages, they are giving full expression to a long-standing tradition whereby a language is construed as a system of entities that can presumably be dealt with on its own terms. The legacy of traditional philology is textual. Writing seems to have been responsible for the view, strengthened later by sound recording, that the physical effects of verbal behavior are the stuff of which languages are made. Numerous everyday expressions perpetuate the resulting view of language as a tool or instrument. But the modern analyst should be able to make the distinction. For all its emphasis on spoken language, structural linguistics has followed in the same tradition. The development of ever more refined descriptive techniques has relied heavily on the preliminary transcription of recorded samples of speech. That leaves the analyst with data, say, the dependent variable, usually two steps removed from their original setting. Structuralists emphasize the notion of "system"; they necessarily capitalize on form. Form, not meaning, lends itself to systematic analysis (at least in principle). It has been said that linguistics can be scientific without being semantic. Meaning is reckoned with, at best, on the basis of posited formal relations. But meaning proves as inescapable as it proves elusive. The realm of meaning is the realm of the independent variables: to keep form and meaning apart is to retain, if not actually strengthen, traditional dualisms. It is a short step from there to some form of mentalism.